Upaya Peningkatan Hasil Belajar IPA Materi Zat dan Perubahannya dengan Metode Eksperimen Pada Siswa Kelas V Sekolah Dasar Negeri 2 Kaliwulu Kecamatan Plered - Shulkhah Shulkhah; Lusiani Lusiani; Febriyansyah Febriyansyah (Jurnal IAI Bunga Bangsa Cirebon, 2021)
The effectiveness of learning that boils down to mastery of learning material to the maximum in children is more determined by the ability of teachers to package a learning activity. If all teachers realize that meaningful learning processes and optimal results affect the ability of children to deal with problems in the future, then every time a teacher plans to prepare a lesson plan will try to create a scenario that can arouse student motivation. The purpose of this paper is